Beyond Distracted Eating: Cognitive Distraction Downregulates Odor Pleasantness and Interacts with Weight Status - Ruda, Iryna; Chellapandian, Deepak Charles; Rott, Marlene; Scheid, Selina; Freiherr, Jessica (Nutrients, 2024)
Considering the widespread issue of distracted eating, our study investigates how cognitive distraction influences the sensory perception of food-related odors among individuals with varying weight statuses. We conducted an exploratory, randomized, and cross-sectional experimental study, using the Tetris game to simulate real-life cognitive distraction, incorporating two distraction levels (low and high) and presenting five distinct odors. A total of 59 participants, categorized into a lean (n = 30) and overweight/obese group (n = 29) based on their body mass index (BMI), received odor stimuli while playing Tetris at low and high difficulty, corresponding to low and high distraction levels, respectively. Participants subsequently rated odor intensity and pleasantness under the two cognitive distraction conditions. Respiratory movements were monitored to ensure accurate olfactory stimulation. Our findings revealed no significant difference in odor intensity ratings across distraction levels (p = 0.903). However, there was a significant reduction in odor pleasantness under high cognitive distraction (p = 0.007), more pronounced in lean participants compared to those with an overweight status (p = 0.035). Additionally, an interaction between gender and cognitive distraction effects was observed in odor pleasantness perception. The differential effects of distraction across weight-status groups and genders are discussed in the context of hedonic motivation and compensatory mechanisms. This study sheds light onto the sensory mechanisms underlying distracted eating and could inform more personalized strategies for promoting healthier eating habits in a world dominated by distractions.
CRIS-Team Scopus Importer:2024-09-20
Keywords: distracted eating; hedonic eating; obesity; odor intensity; odor perception; odor pleasantness

The impact of cognitive distraction on gustatory perception in volunteers with obesity - Ruda, Iryna; Chellapandian, Deepak Charles; Freiherr, Jessica (Scientific Reports, 2024)
Obesity, a global health challenge, is influenced by biological, behavioral, socioeconomical, and environmental factors. In our technology-driven world, distracted eating is prevalent, yet neurocognitive mechanisms behind it remain poorly understood. This study targets individuals with overweight and obesity, exploring taste perception under distraction comprehensively. Participants formed two distinct groups based on their Body Mass Index (BMI), lean and overweight/obese. During the experiment participants received gustatory stimuli while playing a Tetris game of various difficulty levels. Participants rated taste intensity and pleasantness, with linear mixed models analyzing distraction effects. Results confirmed that high distraction levels reduced perception of taste intensity (p = 0.017) and taste pleasantness (p = 0.022), with variations influenced by gender and weight status. Individuals in the overweight/obese group exhibited most profound intensity changes during distraction (p = 0.01). Taste sensitivity ratings positively correlated with BMI interacting with gender (male r = 0.227, p < 0.001; female r = 0.101, p < 0.001). Overall across both groups, female participants demonstrated higher taste sensitivity compared to male participants (p < 0.001). This study highlights the impact of cognitive distraction during consumption on taste perception, particularly in relation to weight status and gender, underscoring their significant roles in this interplay.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Distracted eating; Gustatory perception; Intensity; Obesity; Pleasantness